Some Methods for Finding a Solution in Partially Defined Functional Neural Networks Given by Declarations - Betin, V. N.; Ivashchenko, V. A.; Suprun, A. P. (Automatic documentation and mathematical linguistics, 2025)
The paper considers the features of an algorithm for finding a solution in the formalism of functional neural networks (FN-networks), where the knowledge base and description of the initial problem contain concepts that are defined by partially defined FN-networks with a regular structure, in the form of enumerations of sets of the same type of objects and fragments of the same structure, when their number is unknown and possibly infinite.